Cybersecurity and Its Implications for Freedom of Expression in Germany’s Digital Media Landscape - Sophie Müller (Journal of Linguistics and Communication Studies, 2024)
This paper explores the delicate balance between cybersecurity measures and freedom of expression within Germany’s digital media landscape, highlighting the complexities and challenges of aligning security initiatives with the preservation of democratic values. Through an examination of Germany’s cybersecurity framework, the impact of security measures on digital expression, and case studies such as the use of state-sponsored surveillance and the Network Enforcement Act (NetzDG), this study underscores the nuanced interplay between safeguarding digital infrastructure and upholding the rights to freedom of expression and information. It proposes a multifaceted framework for achieving this balance, emphasizing transparency, proportionality, democratic alignment, collaborative policymaking, ethical considerations, international cooperation, and education. By addressing the imperative of protecting digital spaces from cyber threats while ensuring the free flow of ideas, this paper contributes to the ongoing discourse on crafting a digital ecosystem that supports both security and democratic freedoms.